2023
DOI: 10.4018/jgim.332861
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Digital Agility and Digital Transformation Leadership

Anugamini Priya Srivastava,
Mohit Yadav,
Rohit Yadav
et al.

Abstract: This study aims to explore and examine an integrated model predicting digital agility in higher education institutions. In the exploratory phase, semi-structured interviews were conducted with the heads of the institutions to understand their challenges in ensuring digital agility at work in higher education institutions. In the second phase, the integrated model derived from codes taken from interview responses was developed. The first study round identified factors affecting digital agility from word cloud a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Studies have shown that the workforce's perception of the DT-oriented leadership behavior (Srivastava et al, 2023) affects their responses to change, including desirable (affective, cognitive, and behavioral) trust responses and undesirable (affective, cognitive, and behavioral) resistance to change (Weber et al, 2022). When the workforce perceives that their leaders are committed, proactively track digital trends, and have a clear digital strategy to achieve a digital vision, trust in their leadership is nurtured.…”
Section: Readiness To Change and Digital Transformationmentioning
confidence: 99%
“…Studies have shown that the workforce's perception of the DT-oriented leadership behavior (Srivastava et al, 2023) affects their responses to change, including desirable (affective, cognitive, and behavioral) trust responses and undesirable (affective, cognitive, and behavioral) resistance to change (Weber et al, 2022). When the workforce perceives that their leaders are committed, proactively track digital trends, and have a clear digital strategy to achieve a digital vision, trust in their leadership is nurtured.…”
Section: Readiness To Change and Digital Transformationmentioning
confidence: 99%